A kind of anti-penetration ultra-high performance concrete based on alumina modified aggregate and its preparation method and application
By using alumina modified aggregate in UHPC and using its multiple energy absorption mechanism, the problem of insufficient anti-invasion performance of UHPC is solved, significantly improving its anti-invasion performance and strength balance, and is suitable for military and civil protection projects.
Patent Information
- Application Number
- CN202411921293.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-25
AI Technical Summary
Existing ultra-high performance concrete (UHPC) is not significantly better than ordinary high-strength concrete in terms of infiltration resistance, resulting in limited application in protective projects requiring high infiltration resistance.
Alumina powder is used to modify ordinary aggregates, and alumina modified aggregate with core-shell structure is prepared, and it is introduced into UHPC. The concrete's anti-invasion performance is improved through the multiple energy absorption mechanism of the alumina layer.
While maintaining UHPC's extremely high strength, its anti-invasion performance is significantly improved, the failure mode under high-speed impact is changed, the depth of concrete penetrated, and new ideas and technical ways are provided to improve UHPC's anti-invasion performance.
Smart Images

Figure CN119349963B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and specifically relates to an anti-penetration ultra-high performance concrete based on alumina modified aggregate, and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Ultra-High Performance Concrete (UHPC) has extremely high strength and durability. Its strength is significantly higher than that of ordinary high-strength concrete, and it has become one of the most promising construction materials in protective engineering. However, its anti-penetration performance is not significantly better than that of ordinary high-strength concrete. Compared with ordinary high-strength concrete, the relatively unbalanced strength and anti-penetration performance limits the application of UHPC in protective engineering that requires high anti-penetration performance.
[0004] Existing methods to improve the penetration resistance of UHPC include: using high-strength and high-hardness aggregates, such as corundum and silicon carbide aggregates. These aggregates can effectively improve the penetration resistance of UHPC due to their extremely high strength and hardness. However, compared with ordinary aggregates, the cost of high-strength and high-hardness aggregates such as corundum and silicon carbide is particularly high, which limits their large-scale promotion and application in protective engineering. In order to improve the penetration resistance of UHPC under the action of high-speed projectiles, its material composition and structure still need to be further optimized. Summary of the invention
[0005] In order to address the deficiencies of the prior art, the purpose of the present invention is to provide an anti-penetration ultra-high performance concrete based on alumina modified aggregate and a preparation method and application thereof, by modifying ordinary aggregates with alumina powder to enhance the anti-penetration performance of UHPC, so that the balance between strength and anti-penetration performance is improved while retaining high mechanical properties.
[0006] In order to achieve the above object, the technical solution of the present invention is:
[0007] In a first aspect, the present invention provides an anti-penetration ultra-high performance concrete based on alumina modified aggregate, which is prepared from the following raw materials in parts by weight:
[0008] 360-520 parts of cement, 36-52 parts of silica fume, 36-52 parts of fly ash, 800-1000 parts of fine aggregate, 800-1000 parts of alumina modified aggregate with a particle size of 3-5 mm, 39-78 parts of steel fiber, 120-130 parts of water and 5-10 parts of high-efficiency water reducing agent;
[0009] The alumina modified aggregate has a core-shell structure, wherein the aggregate is the core and the outer side of the aggregate is covered with a sintered alumina shell. The alumina modified aggregate is prepared from the following raw materials in parts by weight: 50-80 parts of alumina powder, 100 parts of aggregate and 2-5 parts of a binder.
[0010] In a second aspect, the method for preparing the above-mentioned anti-penetration ultra-high performance concrete based on alumina modified aggregate comprises the following steps:
[0011] S1. Add a binder to the surface of aggregate with a set particle size, then mix and stir with alumina powder until the particle size grows to a set range, and then dry and compact;
[0012] S2, steam hydrating the compacted aggregate, drying it, and sintering it at 600-700°C for 40-45 minutes to obtain alumina modified aggregate;
[0013] S3, dry-mixing cement, fly ash, silica fume and fine aggregate, then adding water reducer and water accounting for 70% of the total water volume, and stirring to obtain a uniform slurry;
[0014] S4, adding the alumina modified aggregate obtained in S2 to the uniform slurry, stirring until the uniform slurry uniformly covers the alumina modified aggregate, then adding 30% of the total water and stirring, then adding steel fiber, stirring to obtain a mixture;
[0015] S5. Stir the mixture and pour it into shape, then cure it to the specified age.
[0016] In a third aspect, the applications of the above-mentioned penetration-resistant ultra-high performance concrete based on alumina modified aggregate and / or the penetration-resistant ultra-high performance concrete obtained by the preparation method of the penetration-resistant ultra-high performance concrete based on alumina modified aggregate include: applications in military protection projects or applications in civil protection projects.
[0017] The beneficial effects of the present invention are:
[0018] 1. The present invention introduces alumina-modified aggregates with a core-shell structure into UHPC. The core-shell structure composed of alumina and aggregates not only improves the strength and hardness of the material, but also effectively absorbs and disperses the impact energy through the alumina layer, effectively changing the failure mode of UHPC under high-speed impact. The multiple energy absorption mechanisms of alumina-modified aggregates include: plastic deformation of the alumina layer, crack deflection and toughening, interface energy absorption, microcrack formation and expansion retardation, and coarse aggregate self-crushing energy absorption. These mechanisms can effectively absorb and dissipate impact energy through synergistic effects, prevent crack generation and expansion, reduce the penetration depth of concrete under high-speed impact, and significantly improve its anti-penetration performance while maintaining the extremely high strength of UHPC.
[0019] 2. The preparation method of the alumina modified aggregate of the present invention is simple and easy, and is suitable for large-scale production and engineering applications. The performance of the alumina modified aggregate can be further improved by optimizing the formula and process parameters. The successful application of alumina modified aggregate provides a new idea and technical approach for the anti-penetration performance of UHPC, and can be widely used in military protection projects and civil protection projects. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0021] Figure 1 It is a schematic diagram of the technical route in a specific implementation manner of the present invention;
[0022] Figure 2 It is a flow chart of the preparation of ultra-high performance concrete of Example 1 in a specific implementation manner of the present invention. DETAILED DESCRIPTION
[0023] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0024] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0025] A typical embodiment of the present invention provides an anti-penetration ultra-high performance concrete based on alumina modified aggregate, which is prepared from the following raw materials in parts by weight:
[0026] 360-520 parts of cement, 36-52 parts of silica fume, 36-52 parts of fly ash, 800-1000 parts of fine aggregate, 800-1000 parts of alumina modified aggregate with a particle size of 3-5 mm, 39-78 parts of steel fiber, 120-130 parts of water and 5-10 parts of high-efficiency water reducing agent;
[0027] The alumina modified aggregate has a core-shell structure, wherein the aggregate is the core and the outer side of the aggregate is covered with a sintered alumina shell. The alumina modified aggregate is prepared from the following raw materials in parts by weight: 50-80 parts of alumina powder, 100 parts of aggregate and 2-5 parts of a binder.
[0028] Among the above raw materials, the alumina modified aggregate has a core-shell structure, and the sintered alumina shell has multiple energy absorption mechanisms, including plastic deformation of the alumina layer, crack deflection and toughening, interface energy absorption, and microcrack formation and expansion retardation. These mechanisms work synergistically to significantly improve the penetration resistance of UHPC while maintaining its extremely high strength.
[0029] Optionally, in the alumina modified aggregate, the aggregate particle size is 3~5mm, the thickness of the sintered alumina shell is 0.2~0.3mm; the alumina powder particle size range is 1~10μm; in the alumina powder, the proportion of aluminum oxide component is not less than 90wt%, which can provide excellent energy absorption capacity and high hardness after sintering.
[0030] Optionally, the aggregate is a natural rock material selected from one or more of basalt particles and granite.
[0031] Optionally, the adhesive is ammonium bicarbonate and sodium carbonate mixed in a mass ratio of 5:4 to prepare an aqueous solution with a mass concentration of 0.3% to 1%. As a binder, it can effectively bond the aluminum oxide powder to ensure its shell shape.
[0032] Optionally, the cement is 52.5 grade ordinary Portland cement.
[0033] Optionally, the mass percentage of silicon dioxide in the silica ash is not less than 97%, the volcanic ash activity index of the silica ash is greater than 95%, the specific surface area is greater than 21.0 m² / g, and the density is 2.20 g / cm³.
[0034] Optionally, the fly ash is Class I fly ash, with a combustion vector of less than 3.0%, a specific surface area of more than 1000 cm² / g, and main components including silicon oxide and aluminum oxide.
[0035] Optionally, the fine aggregate is natural river sand with a fineness modulus of 2.3 to 3.0 and a maximum particle size of 4.75 mm, which is smaller than the particle size of the alumina modified aggregate, and a continuous grading effect can be obtained.
[0036] Optionally, the steel fiber is a straight steel fiber with a length specification of 13 mm.
[0037] Optionally, the high-efficiency water reducer is a polycarboxylate water reducer with a water reduction rate of >30%.
[0038] The method for preparing the above-mentioned anti-penetration ultra-high performance concrete based on alumina modified aggregate comprises the following steps:
[0039] S1. Add a binder to the surface of aggregate with a set particle size, then mix and stir with alumina powder until the particle size grows to a set range, and then dry and compact;
[0040] S2, steam hydrating the compacted aggregate and drying it, and then sintering it at 600-700° C. for 40-45 minutes to obtain alumina modified aggregate;
[0041] S3, dry-mixing cement, fly ash, silica fume and fine aggregate, then adding water reducer and water, and stirring to obtain a uniform slurry;
[0042] S4, adding the alumina modified aggregate obtained in S2 to the uniform slurry, stirring until the uniform slurry uniformly covers the alumina modified aggregate, then adding water and stirring, then adding steel fiber, and stirring to obtain a mixture;
[0043] S5. Stir the mixture and pour it into shape, then cure it to the specified age.
[0044] Optionally, in S1, the aggregate is crushed and sieved to obtain aggregate particles of a set particle size, and then the aggregate particles are washed to remove mud, dust and impurities on the surface, and then dried.
[0045] Optionally, in S1, the adhesive is an aqueous solution of ammonium bicarbonate and sodium carbonate in a mass ratio of 5:4, and a mass concentration of 0.3-1.0%. The cleaned and dried aggregate particles are immersed in the adhesive and stirred to make the adhesive evenly cover the surface of the aggregate particles. The aggregate particles with the adhesive added are then mixed and stirred with alumina powder to make the alumina powder adhere to the surface of the aggregate particles. Aggregate particles with alumina powder successfully adhered to the surface are screened out by screening. The addition of adhesive and the adhesion of alumina powder are repeated multiple times, and the falling of alumina powder is reduced by controlling the concentration and amount of the adhesive, strengthening the drying process and optimizing the stirring method to ensure the bonding effect and make the alumina powder layer reach a set thickness.
[0046] Optionally, in S1, the compaction pressure is 20-30 MPa, and the compaction time is 5-10 minutes.
[0047] Optionally, in S2, the steam hydration treatment method is: performing at a high temperature of 90-100°C for 5-6 hours to enhance the bonding effect, and then drying at 100-110°C for 4-6 hours to ensure that the internal moisture is completely evaporated.
[0048] Optionally, in S2, the material is cooled with the furnace after sintering to avoid cracking of the material due to sudden temperature change.
[0049] Optionally, in S3, the dry mixing speed is 60 r / min, the dry mixing time is 1-2 min, the mixing time after adding water is 2-4 min, and the mixing speed is 120 r / min.
[0050] Optionally, in S4, after adding alumina modified aggregate, the stirring speed is 120r / min, and the stirring time is 1-2min; after adding water, the stirring speed is 120r / min, and the stirring time is 2-3min; after evenly spreading steel fiber, the stirring speed is 60r / min, and the stirring time is 2.5-4min.
[0051] Optionally, in S5, the stirring speed before pouring is 150r / min, the stirring time is 2-3min, the bubbles in the concrete are removed after pouring and forming, and after initial forming, the concrete is allowed to stand and cure for 24h under standard curing conditions to ensure initial hardening, and after initial hardening, standard curing is carried out to the specified age.
[0052] Optionally, in S5, the curing conditions after initial hardening are: temperature of 20±2°C and humidity ≥95%.
[0053] Preparation Example 1
[0054] A method for preparing an alumina modified aggregate comprises the following steps:
[0055] Basalt from natural rock materials is used as aggregate, and a jaw crusher or impact crusher is used to crush the aggregate into small particles. Vibrating screening equipment is used to screen out aggregate particles with a particle size of 3-5 mm. A high-pressure water gun or stone washing machine is used to clean and remove mud, dust and impurities on the surface, and then it is dried at 100°C for 4 hours to ensure that the surface is completely dry.
[0056] After ammonium bicarbonate and sodium carbonate are mixed in a mass ratio of 5:4, the amount of water added is adjusted according to the surface characteristics of the aggregate particles and the bonding requirements to prepare a binder with a mass concentration of 0.5%.
[0057] Place the dried basalt aggregate particles in a moistening amount of binder and stir for 15 minutes to ensure that the surface of each aggregate particle is evenly coated with the binder. Then, place the aggregate particles in a stirrer filled with alumina powder and stir at a speed of 60-100r / min for 20 minutes to make the surface of the aggregate particles evenly coated with alumina powder. Then, use a 100-150 mesh sieve to sieve out the alumina powder to obtain aggregate particles with alumina powder adhered to the surface, and then dry them.
[0058] The dried aggregate particles with alumina powder adhered to the surface are mixed with a binder, stirred, screened and dried three times to obtain aggregate particles with a set particle size and an alumina powder layer. The aggregate particles with the alumina powder layer are placed in a special mold to ensure that the individual particles are dispersed from each other and avoid rolling. A hydraulic press is used to apply a pressure of 20 MPa for 5 minutes to ensure that the alumina powder and basalt are tightly combined.
[0059] The compacted particles were steam-hydrated at 90 °C for 5 h to enhance the bonding effect; then dried at 100 °C for 4 h to ensure complete evaporation of the internal moisture.
[0060] The dried particles were sintered at 700°C for 40 minutes and gradually cooled in the furnace after sintering to avoid cracking of the material due to sudden temperature change, and finally alumina modified aggregate was obtained.
[0061] After testing, the prepared alumina modified aggregate was a single-core structure with a particle size of 3~5mm. The thickness of the alumina shell after sintering was 0.2~0.3mm, and no melt crystallization occurred. The compressive strength of the prepared alumina modified aggregate reached more than 150MPa, showing excellent impact resistance compared with basalt coarse aggregate.
[0062] Preparation Example 2
[0063] A method for preparing an alumina-modified aggregate, which differs from Preparation Example 1 in that basalt aggregate is replaced by granite aggregate; the prepared alumina-modified aggregate has a single-core structure, a particle size of 3-5 mm, a thickness of an alumina shell of 0.2-0.3 mm after sintering, and no melt crystallization occurs; the prepared alumina-modified aggregate has a compressive strength of more than 120 MPa, and exhibits excellent impact resistance compared with granite coarse aggregate.
[0064] Example 1
[0065] A penetration-resistant ultra-high performance concrete based on alumina-modified aggregate comprises the following raw materials in parts by mass: 400 parts of cement, 40 parts of silica fume, 40 parts of fly ash, 900 parts of river sand, 900 parts of alumina-modified aggregate obtained in Preparation Example 1, 39 parts of steel fiber, 120 parts of water, and 8 parts of a water reducer.
[0066] The preparation method comprises:
[0067] First, add cement, fly ash, silica fume and river sand into a mixing equipment in proportion and dry mix them at a speed of 60r / min for 1min. After dry mixing, add 70% of the total water volume and water reducer, and stir at a speed of 120r / min for 2min until a uniform slurry is formed.
[0068] Then, the alumina-modified aggregate obtained in Preparation Example 1 was added to the mixing equipment and stirred at a stirring speed of 120 r / min for 2 minutes until the alumina-modified aggregate was uniformly wrapped by the slurry; then, the remaining 30% of the total water was added and stirred at a stirring speed of 120 r / min for 3 minutes to make the mixture uniform; then, the steel fibers were gradually and evenly sprinkled into the mixer and stirred at a stirring speed of 60 r / min for 3 minutes to ensure that the steel fibers were evenly distributed in the mixture.
[0069] Before pouring, stir at a speed of 150r / min for 3 minutes. After pouring, remove internal bubbles. After initial forming, let it stand under standard curing conditions for 24 hours to ensure initial hardening. After initial hardening, carry out standard curing to the specified age.
[0070] Example 2
[0071] A penetration-resistant ultra-high performance concrete based on alumina-modified aggregate, which differs from Example 1 in that the alumina-modified aggregate obtained in Preparation Example 1 is replaced by the alumina-modified aggregate obtained in Preparation Example 2, and a sample is obtained according to the same preparation method.
[0072] Comparative Example 1
[0073] A penetration-resistant ultra-high performance concrete containing basalt aggregate, the raw materials comprising the following raw materials in parts by mass: 400 parts of cement, 40 parts of silica fume, 40 parts of fly ash, 900 parts of river sand, 900 parts of basalt aggregate, 39 parts of steel fiber, 120 parts of water, and 8 parts of water reducing agent.
[0074] The specification of the basalt aggregate is: particle size 3~5mm, which is the same as the particle size of the alumina modified aggregate used in Example 1.
[0075] The other raw material requirements are the same as those in Example 1 and are prepared according to the same preparation method as in Example 1.
[0076] Comparative Example 2
[0077] A penetration-resistant ultra-high performance concrete containing granite aggregates, the raw materials comprising the following raw materials in parts by mass: 400 parts of cement, 40 parts of silica fume, 40 parts of fly ash, 900 parts of river sand, 900 parts of granite aggregates, 39 parts of steel fibers, 120 parts of water, and 8 parts of water reducing agent.
[0078] The specifications of the granite aggregate are: particle size 3~5mm, which is the same as the particle size of the alumina modified aggregate used in Example 2.
[0079] The other raw material requirements are the same as those in Example 1 and are prepared according to the same preparation method as in Example 1.
[0080] Comparative Example 3
[0081] An ultra-high performance concrete comprises the following raw materials in parts by weight: 400 parts of cement, 40 parts of silica fume, 40 parts of fly ash, 900 parts of river sand, 39 parts of steel fiber, 120 parts of water, and 8 parts of water reducing agent.
[0082] The difference from Comparative Example 1 is that the basalt aggregate is eliminated.
[0083] The other raw material requirements are the same as those in Comparative Example 1 and are prepared according to the same preparation method as Comparative Example 1.
[0084] Comparative Example 4
[0085] The invention discloses an anti-penetration ultra-high performance concrete, wherein the raw materials include the following raw materials in parts by weight: 400 parts of cement, 40 parts of silica fume, 40 parts of fly ash, 900 parts of river sand, 900 parts of sintered alumina aggregate, 39 parts of steel fiber, 120 parts of water, and 8 parts of water reducing agent.
[0086] The specifications of the sintered alumina aggregate are: particle size 3~5mm, which is the same as the particle size of the alumina modified aggregate used in Example 1. The sintered alumina aggregate is alumina powder with Al2O3≥90wt% sintered at 600-700℃, and has a porous structure. Mechanical property tests show that its compressive strength is about 150-180MPa, and it has high hardness and impact resistance.
[0087] The other raw material requirements are the same as those in Example 1 and are prepared according to the same preparation method as in Example 1.
[0088] Test example
[0089] Conventional mechanical tests and high-speed projectile penetration resistance tests were performed on the materials of Examples 1-2 and Comparative Examples 1-4.
[0090] Conventional mechanical experiments include: compressive strength test.
[0091] The test conditions for high-speed projectile penetration resistance include the following:
[0092] Sample preparation: The test object is prepared as a prismatic target with a size of 550×550×400mm³ (thickness in the ballistic direction is 400mm), using a pointed egg-shaped projectile with a diameter of 28mm and a projectile material of 30CrMnSiNi2A high-strength alloy steel (yield strength of 1370-1466MPa, ultimate strength of 1770MPa, Rockwell hardness of 55HRC).
[0093] Test device: The test device mainly includes a barrel, a high-speed camera and a target. The barrel is used to fire bullets and hit the target in front. The bullet impact speed is set to 400m / s. The high-speed camera is installed on the side of the trajectory to capture the movement of the projectile.
[0094] Damage assessment: The degree of damage caused by high-speed projectiles to the concrete target is assessed by measuring the penetration depth, crater diameter and crater volume of the target.
[0095] Among them, penetration depth refers to the distance from the impact surface of the target to the deepest point of the crater;
[0096] The crater diameter is the diameter of an equivalent circle with the same area as the target crater;
[0097] The crater volume refers to the volume of the target crater.
[0098] The results of conventional mechanical experiments and high-speed projectile penetration resistance tests are shown in Table 1.
[0099] Table 1 Results of conventional mechanical tests and high-speed projectile penetration resistance tests
[0100]
[0101] The penetration depth of the ultra-high performance concrete containing alumina-modified basalt aggregate in Example 1 is 58 mm under the action of a 28 mm diameter projectile and a target velocity of 400 m / s; compared with the unmodified basalt UHPC in Comparative Example 1 (penetration depth 63 mm), the penetration depth is reduced by 7.9%; compared with the unmodified granite UHPC in Comparative Example 2 (penetration depth 66 mm), the penetration depth is reduced by 12.1%; compared with the traditional UHPC in Comparative Example 3 (penetration depth 70 mm), the penetration depth is reduced by 17.1%; compared with the sintered alumina aggregate UHPC in Comparative Example 4 (penetration depth 59 mm), the penetration depth is reduced by 1.7%.
[0102] The penetration depth of the ultra-high performance concrete using alumina-modified granite aggregate in Example 2 under the same conditions is 60 mm; compared with the unmodified basalt UHPC in Comparative Example 1 (penetration depth 63 mm), the penetration depth is reduced by 4.8%; compared with the unmodified granite UHPC in Comparative Example 2 (penetration depth 66 mm), the penetration depth is reduced by 9.1%; compared with the traditional UHPC in Comparative Example 3 (penetration depth 70 mm), the penetration depth is reduced by 14.3%; compared with the sintered alumina aggregate UHPC in Comparative Example 4 (penetration depth 59 mm), the penetration depth is increased by 1.7%.
[0103] It can be seen from the test results that the target bodies of Examples 1 and 2 have excellent mechanical properties and anti-penetration performance, especially in terms of penetration depth. Alumina modified aggregate significantly improves the anti-penetration performance of UHPC: the compressive strengths of Examples 1 and 2 are 180MPa and 175MPa, respectively, which are significantly higher than those of Comparative Examples 1, 2 and 3, and show smaller pit diameters and volumes in the penetration test. Compared with Comparative Example 4, although Examples 1 and 2 have similar anti-penetration performance, Comparative Example 4 has a slightly lower compressive strength (about 170MPa), and is insufficient in wear resistance and impact resistance. In practical applications, Comparative Example 4 uses sintered alumina aggregate, which has a higher hardness, but its porous structure and poor impact toughness make it more prone to crack propagation under high stress and multiple impacts, and its impact energy absorption efficiency is also low. In summary, the alumina modified aggregate of the present invention significantly improves the penetration resistance of UHPC through multiple energy absorption mechanisms, such as plastic deformation, crack deflection and toughening of the alumina layer, and is superior to Comparative Example 4 in long-term penetration resistance performance. At the same time, it has higher compressive strength and better durability and fatigue resistance.
[0104] The above advantages make alumina modified aggregates suitable for use as modern new protective materials with broad application prospects. Applications in military protection projects include: use in military fortifications, missile launch sites, strategic weapons storage, etc., which can provide excellent anti-penetration and anti-explosion performance. Applications in civil protection projects include: use in war-ready roads, protective buildings, key infrastructure, etc., which can significantly improve its impact resistance and anti-destruction capabilities.
[0105] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An anti-penetration ultra-high performance concrete based on alumina modified aggregate, characterized in that: The invention is prepared from the following raw materials in parts by mass: 360-520 parts of cement, 36-52 parts of silica fume, 36-52 parts of fly ash, 800-1000 parts of fine aggregate, 800-1000 parts of alumina modified aggregate with a particle size of 3-5 mm, 39-78 parts of steel fiber, 120-130 parts of water and 5-10 parts of water reducer; the alumina modified aggregate is a core-shell structure, the aggregate is the core, and the outer side of the aggregate is covered with a sintered alumina shell. The alumina modified aggregate is prepared from the following raw materials in parts by mass: 50-80 parts of alumina powder, 100 parts of aggregate and 2-5 parts of binder.
2. The anti-penetration ultra-high performance concrete based on alumina modified aggregate according to claim 1, characterized in that: In the alumina modified aggregate, the aggregate particle size is 3~5mm, and the thickness of the sintered alumina shell is 0.2~0.3mm.
3. The anti-penetration ultra-high performance concrete based on alumina modified aggregate according to claim 1, characterized in that: The aggregate in the alumina modified aggregate is a natural rock material, selected from one or more of basalt particles and granite.
4. The anti-penetration ultra-high performance concrete based on alumina modified aggregate according to claim 1, characterized in that: The fine aggregate is natural river sand.
5. The anti-penetration ultra-high performance concrete based on alumina modified aggregate according to claim 1, characterized in that: The particle size of the alumina powder ranges from 1 to 10 μm; in the alumina powder, Al2O3≥90wt%.
6. The anti-penetration ultra-high performance concrete based on alumina modified aggregate according to claim 1, characterized in that: The mass percentage of silicon dioxide in the silica ash is not less than 97%, the volcanic ash activity index of the silica ash is greater than 95%, and the specific surface area is greater than 21.0m² / g; the fly ash is Class I fly ash, the loss on ignition is less than 3.0%, and the specific surface area is greater than 1000cm² / g.
7. The anti-penetration ultra-high performance concrete based on alumina modified aggregate according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate is greater than 30%.
8. A method for preparing the anti-penetration ultra-high performance concrete based on alumina modified aggregate according to any one of claims 1 to 7, characterized in that the steps include: S1. Add a binder to the surface of aggregate with a set particle size, then mix and stir with alumina powder until the particle size grows to a set range, and then dry and compact; S2, steam hydrating the compacted aggregate and drying it, and then sintering it at 600-700° C. for 40-45 minutes to obtain alumina modified aggregate; S3, dry-mixing cement, fly ash, silica fume and fine aggregate, then adding water reducer and water, and stirring to obtain a uniform slurry; S4, adding the alumina modified aggregate obtained in S2 to the uniform slurry, stirring until the uniform slurry uniformly covers the alumina modified aggregate, then adding water and stirring, then adding steel fiber, and stirring to obtain a mixture; S5. Stir the mixture and pour it into shape, then cure it to the specified age.
9. The preparation method according to claim 8, characterized in that: In S1, the compaction pressure is 20~30MPa, and the compaction time is 5~10min; in S2, the steam hydration treatment method is: at a high temperature of 90~100℃ for 5~6h, then dried at 100-110℃ for 4~6h, and cooled with the furnace after sintering; in S3, the dry mixing speed is 60r / min, the dry mixing time is 1-2min, the stirring time after adding water is 2-4min, and the stirring speed is 120r / min; in S4, the stirring speed is 120r / min after adding alumina modified aggregate, and the stirring time is 1-2min; the stirring speed is 120r / min after adding water, and the stirring time is 2-3min; after evenly spreading steel fiber, the stirring speed is 60r / min, and the stirring time is 2.5-4min.
10. An application of the anti-penetration ultra-high performance concrete based on alumina modified aggregate as claimed in any one of claims 1 to 7 or the anti-penetration ultra-high performance concrete prepared by the preparation method as claimed in any one of claims 8 to 9, characterized in that: The applications include: applications in military protection projects or applications in civil protection projects.
Citation Information
Patent Citations
Concrete anti-penetration structure and preparation method thereof
CN112012548A
High-temperature-resistant ultra-high-performance concrete and preparation method thereof
CN118324475A